Power approximation of the transmission disequilibrium test - Germanas, Šarūnas; Jakaitienė, Audronė (Lietuvos matematikos rinkinys, 2012)
In this paper we apply Poisson distribution in order to approximate the power of the Transmission Disequilibrium Test (TDT). In this research we calculated the power of the TDT for different values of sample size n and different values of allele transmission frequencies p. The research showed that Poisson approximation have smaller errors than Normal approximation when the power is between 0.8 and 0.95 and sample size m is equal or bigger than 50.